Kajian Teori: Pandangan Filosofi Matematika pada Pengembangan Tugas Proyek - Andriani, Ulfia Churidatul; Esty Saraswati Nur Hartaningrum (Fakultas Sains dan Teknologi Universitas Kanjuruhan Malang, 2025)
This study aims to explore the views of the philosophy of mathematics in the context of developing project assignments in mathematics education. Through a qualitative approach based on a literature review, this study analyzes various theories and perspectives related to the philosophy of mathematics, including the pragmatic and constructivist approaches. The main focus of this study is how the philosophy of mathematics influences project-based learning and the development of project assignments based on the inquiry method. This study uses sources from various academic databases, such as Google Scholar, ResearchGate, and JSTOR, with a range of articles from 2000 to 2023. The results of the analysis show that the application of the philosophy of mathematics, especially constructivism and the pragmatic approach, plays an important role in encouraging collaboration, problem-solving skills, and the development of artifacts in project assignments. These findings provide insight that project assignments can be an effective means of developing mathematical understanding that is applicable and relevant to students' real-life contexts Kata Kunci: philosophy of mathematics, project assignments, project-based learning, mathematics education, constructivism